Music/ideology: Resisting the aesthetic - Krims, Adam (Amsterdam Routledge, 1998)
This collection of essays, which reflects the views of music scholars who bring critical theory to bear on the theory and analysis of music, is long overdue. The essayists are not fixated on aesthetics: rather, they focus on the social and psychological concerns that previously had been considered marginal to their subject. "Music/Ideology" is a response to the question "Must the practice of music analysis and music theory always re-inscribe the ideology of aesthetic autonomy?" And, if not, under what circumstances does it re-inscribe that ideology? The responses to these questions should appeal not only to music and cultural theorists, but also to a larger audience engaged in critical theory. Essays by Jean-Francois Lyotard, Alan Street, Richard Littlefield, David Neumeyer, Marion Guck, Suzanne Cusick, David Gramit joke Dame, and Robert Fink.